A Study of Open Access Publishing by NHMRC Grant Recipients - Kirkman, Noreen Suzanne (Curtin University, 2018)
This study is the first comprehensive study to measure open access compliance under Australia’s earliest national-level open access policy, the National Health and Medical Research Council Open Access Policy. The key findings were that over two-thirds of the journal articles were open access, most were in journals with a small number of postprints located in Australian institutional repositories. This study provides a greater understanding of open access publishing under a funder open access mandate.